PEMBELAJARAN FISIKA BERBASIS INKUIRI TERBIMBING DENGAN MENGGUNAKAN LKS UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DITINJAU DARI SIKAP ILMIAH SISWA MADRASAH ALIYAH QAMARUL HUDA BAGU LOMBOK TENGAH - Yuyu Sudarmini; Kosim -; Aos Santosa Hadiwijaya (Jurnal Penelitian Pendidikan IPA, 2015)
This research aimed at 1). Developing learning design of guided inquiry based physics learning using  student worksheet. 2). Knowing the difference  of improvement  of the  critical thinking between students those who learned  using guided inquiry based physics learning and those who learned physics conventionally. 3). Knowing the difference of improvement  of the  critical thinking between students with a highly scientific attitude and those with a low one. 4) Knowing the interaction between learning physics   and scientific attitude toward the improvement of students’ critical thinking skill. The research was conducted through two steps, namely:  1) Development research using Dick’s and Carey’s development model, 2) Experimental research using 2x2 factorial design.  The population of this research was the students of MA Qamarul Huda Bagu, central Lombok, year  eleven.  The sample of the research consisted of 2 classes taken by simple random sampling technique.  Data collection using questioner to know the students’ scientific  attitude, and test to know the students’ critical thinking skill score.  Hypothetical test for experimental research used  two path ANAVA  by using SPSS. The  result of development research was yielded a good learning equipment of the guided inquiry based physics learning using student worksheet. The experimental research showed that: 1) There was difference of improvement of critical thinking skill between the students who got a guided inquiry  physics learning using student worksheet  and those who got conventional learning.  This was shown by value of Ftest=42,480, was higher than that of Ftable=4,11, and the value of sig=000 was lower than 0,05; 2) There was difference of improvement of   critical thinking  skill between the students with a high scientific attitude and those with a low one. This was shown by value of Ftest=13,150, was higher than that of Ftable=4,11, and the value of sig=0,001 was lower than 0,05; 3). There was no interaction between the physics learning (guided inquiry based  using  student worksheet and that of conventionally) and scientific attitude towards the improvement of critical thinking skill. This was shown by value of Ftest=1,277  was lower than that of Ftable=4,11 and value of sig=0,265 was higher than 0,05. It was expected that the guided inquiry based physics learning using student worksheet was combined with other learning models to enhance critical thinking skill more optimal mainly for the abstract materials of physics.Key word: guided inquiry, student worksheet, scientific attitude, critical thinking skill,